PENGARUH EKONOMI KELUARGA TERHADAP PUTUSNYA SEKOLAH ANAK - Muhammad Yusuf (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2017)
This study aims to determine the factors causing children to drop out ofschool and Know the impact of children who dropped out of school andto Know the right steps to overcome the problem of school dropouts inthe Village District Karangagung Palang. Data collection methods usedare interviews and retrieve data from relevant parties. Methods Dataanalysis was done by grouping the results of interview factors of drop outchildren to three factors, namely economic factors, environmental factors,personal factors. Based on the data collected, it was found that the factorscausing drop out were as follows: economic factors, environmentalfactors, personal factors. DOI: https://dx.doi.org/10.17977/UM014v10i22017p099